Photocatalytic Activity and Kinetic Study of Methylene Blue Degradation using N-Doped TiO2 with Zeolite-NaY - Susanti, Indri; Iqbal, Rendy Muhamad; Rachman, Rahadian Abdul; Pradana, Tri Agusta (Universitas PGRI Madiun, 2021)
Methylene blue is the most widely used dye in the industry and it is difficult to be degraded by the microorganism. This research aims to investigate the photocatalytic activity and effects of contact time on the photocatalytic degradation rate of methylene blue by TiO2/Zeolite-NaY and TiO2-N/Zeolite-NaY material based on the kinetic study. The Advanced Oxidative Process (AOP) method was used to degrade methylene blue. Furthermore, the AOP is a degradation process that uses semiconductor material such as TiO2 or modification catalyst of TiO2 to be TiO2/Zeolite-NaY and TiO2-N/Zeolite-NaY. The degradation of methylene blue with catalyst TiO2/Zeolite-NaY and TiO2-N/Zeolite-NaY were tested under UV light for 5, 20, 30, 40, and 50 minutes. The result showed that TiO2/Zeolite-NaY and TiO2-N/Zeolite-NaY had an excellent activity for degrading the dye, which reached up to 99% after 20 and 30 minutes reaction, respectively. Also, a kinetic study of methylene blue degradation on TiO2/Zeolite-NaY and TiO2-N/Zeolite-NaY showed the kinetic models were according to pseudo-second-order.